Nodal price control: a mechanism for transmission network cost allocation - Gil, H.A.; Galiana, F.D.; da Silva, E.L. (IEEE transactions on power systems, 2006)
This paper presents an approach for the allocation of transmission network costs by controlling the nodal electricity prices. The proposed approach introduces generation and nodal injection penalties into the traditional economic dispatch so as to create nodal price differences that recover the required transmission revenue from the resulting congestion rent. As a consequence, the new electricity prices reflect not only the marginal costs of production subject to transmission constraints but also the capital costs of the network. This is the approach commonly adopted with most commodities whose price includes the unit cost of the good itself as well as the transportation cost from the production centers to the final consumer.